THE JURISPRUDENTIAL LANDMARK: ANALYZING THE SCHOLARLY CONTRIBUTIONS OF KHADICHA SULAYMONOVA (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
This article elucidates the life and legacy of Khadicha Sulaymonova, the first female Uzbek jurist, tracing her trajectory from her initial entry into the legal profession to her monumental contributions to the national judicial system and her distinguished diplomatic endeavors on the international stage.